Social solidarity determinant of community nursing achievement in disaster areas: Sequential explanatory mixed methods study - Baso Witman Adiaksa; Syamsu A Kamaruddin; Arlin Adam; Ahmadin Ahmadin (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Social solidarity remains an underexplored determinant in the implementation of community nursing practices, particularly in disaster-prone settings. While prior studies have examined post-disaster social dynamics, limited evidence exists on how social solidarity directly influences the achievement of community nursing interventions. This study aimed to analyze the effect of social solidarity on the achievement of community nursing practice in disaster mitigation contexts. Research Methodology: This study employed a mixed-methods approach with a sequential explanatory design. The quantitative phase used a cross-sectional design with purposive sampling of community members involved in disaster-prone coastal areas. Data were collected using a structured questionnaire and analyzed using univariate tests, Pearson correlation, and linear regression (α = 0.05). The qualitative phase involved in-depth interviews, which were analyzed using thematic analysis to inform the interpretation of quantitative findings. Results: The quantitative findings showed a significant positive relationship between social solidarity and achievement in community nursing practice (r = 0.62; p = 0.001). Regression analysis indicated that social solidarity was a significant predictor (β = 0.45; p < 0.001). Higher levels of social solidarity were associated with increased community participation and improved service coverage. Qualitative findings revealed three key mechanisms: cooperation, trust in healthcare workers, and local leadership, which collectively strengthened implementation outcomes. Conclusion: Social solidarity functions as a critical social determinant that enhances the effectiveness of community nursing practice in disaster settings. Integrating social-based strategies into community health interventions can improve participation, acceptance, and sustainability of care delivery.